Pemberdayaan Ekonomi Masyarakat Kelompok Tani Bunga Di Kecamatan Tomohon Utara Kota Tomohon - Wowiling, Marlein Anita; Rantung, Ventje V; Tulung, Max (JURNAL ILMIAH SOCIETY, 2016)
This study aims to determine the condition of the level of income and the welfare of farmers' groups cut flowers chrysanthemum in Sub District of North Tomohon befor and after empowerment programs. Collecting data using a survey method, ie the entire interview informants to obtaining an overview of the focus and the empirical study variables such as income level and the level of welfare of farmers cut flower chrysanthemum in the village of Kakaskasen, Kakaskasen Satu, Kakaskasen Dua and Kakaskaskasen Tiga. Data were analyzed by examining differences in the population mean two pairs of data, by using the method before and after treatment in which to do comparisons between levels of income and welfare levels before and after the empowerment program. The results of the evaluation in this research note that with empowermment program for farmer group of cut flower chrysanthemum in Tomohon, particularly in Village Kakaskasen, Kakaskasen Satu, Kakaskasen Two and Kakaskasen Kakaskasen Three of Sub District of North Tomohon is affecting the income and welfare of farmers. With the existence of the empowerment program, the farmers' income can be increased, thereby increasing the level of welfare of the farming community. The level of income is the amount of revenue income after business development chrysanthemum cut flowers and other business. Once empowered, revenue increased about five times and welfare of farmers increased about two times